The Protection of Privacy in the Spanish Criminal Code. A Critical Analysis of the Reform of 2015. - García-Magna, Débora (Universidad de Deusto, 2020)
The increase in the use of new technologies and their incorporation into everyday forms of communication has led to the appearance of new risks associated to the transfer of personal data and the publication of sensitive material on social networks. The concern for the protection of privacy in postmodern societies intensifies when the persons involved in this growing traffic of personal information are vulnerable people, such as minors, who also make a particularly intensive use of these new means of communication. After addressing in the first place the evolution of the right to privacy from a jurisprudential and supranational point of view, this research has questioned the decision of the Spanish legislator to criminalize sexting in 2015.
Keywords: Derecho penal - España; Derecho a la intimidad; Privacy; Spanish criminal code; Sexting; Penal reform